The concept of digital justice in the resolution of family disputes - Kirillova , Elena; Grineva , Anna (Interacción y Perspectiva, 2024)
The article examines the concept of digital justice in resolving family disputes. The use of new technologies in judicial activities poses challenges for researchers in defining the main features and components of digital justice. The aim of the research is to consider the implementation of digital technologies in judicial activities related to family disputes, identify the main components and features of digital justice, and propose a concept of digital justice based on gathered characteristics. Research methods are based on the analysis of a limited range of studies, which were selected according to specific parameters and comprehensively examined; analogy method and comparative analysis were also applied. As a result of the conducted research, a concept of digital justice in family disputes has been formed, in which the main components of digital justice are defined: dematerialization of the judicial process, online access to court materials, use of video communication during court proceedings, and application of artificial intelligence in court activities. Features of digital justice have been identified: technological, electronic, remote, organizational, target-oriented, and feature of digital document flow. Principles of digital justice have been developed, which serve as basic ideas and guarantee the effective resolution of disputes in the field of family relations.